Hydrometeorological assessments of the transport of microplastic pellets in the Eastern Mediterranean - Gundogdu, Sedat; Ayat, Berna; Aydogan, Burak; Cevik, Cem; Karaca, Serkan (ELSEVIER, 2022)
Y Microplastic pellets were sampled in May and November 2018 during one-week surveys at 13 coastal beaches in Iskenderun Bay/Turkey. Pellet pollution index (PPI) was calculated for the beaches as a tool to assess beach pollution by microplastic pellets. Hydrometeorological conditions, including wind, current, wave, surface run-off, and precipitation, were examined during 2018 to reveal the effect on the transport of microplastic pellets within the study area. Sea-surface heights, including the astronomical tide and the storm surge and the wave runup heights, were also considered in the analysis to study the extent of hydrodynamic forcing on the beach. Hydrometeorological assessments indicated that the pellet concentrations in the coastal zone are mostly related to wind-induced transport. Three major river discharges are considered as the main source of microplastic pellets effluents. A Lagrangian particle transport model was conducted to reveal the possible beaching hotspots of microplastic pellets released from these river mouths. Average microplastic pellets were calculated as 126.04 +/- 54.08 items/m2 for May 2018 and 70.22 +/- 18.25 items/m2 for November 2018. An overall mean PPI for May 2018 was calculated as 1.13, indicating a moderate degree of pellet pollution, and 0.56 for November 2018, indicating a low degree of pellet pollution. The simulations showed that Orontes River effluents affected the inner Iskenderun Bay coasts more than the Seyhan and Ceyhan River.
Keywords: Nurdle; Pellet pollution; Iskenderun Bay; Hydrodynamical model; Lagrangian particle transport model; NE LEVANTINE COAST; PLASTIC POLLUTION; BEACHES; LITTER; BAY; FEATURES; EUROPE; DEBRIS; SCALE; WINDS; Environmental Sciences & Ecology